Comparison of bone health status and physical fitness component between inactive non-bowlers and recreational bowlers - Abdillah, Ahmad Ariff Zaki (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
This study investigated the differences in bone health status and physical fitness component among Malaysian male inactive non-bowlers and recreational tenpin bowlers. A total of 16 participants (mean age= 27.81 ± 8.04 years) were recruited. There were two groups, i.e., inactive non-bowler group (n=8) and tenpin bowlers group (n=8). Participants’ body composition was measured by using a body composition analyser. Isokinetic knee and shoulder extension and flexion muscular peak torque (PT) (strength), peak torque per body weight (PT/BW), and average power (AVG.P) were measured using an isokinetic dynamometer (BIODEX) at 3 different angular velocities, i.e., 60⁰.s-1, 180⁰.s-1 and 300⁰.s-1. A bone sonometer was used to measure bone speed of sound (SOS) which can reflect bone mineral density of radius and tibia bones. Hand grip strength test, back and leg strength test and flexibility test were performed. Independent t-test was performed to determine the differences of the measured parameters between groups. The present study found that there were no statistically significant differences in body weight, body mass index, percentage of body fat and fat-free mass between inactive non-bowler and tenpin bowler groups. Body height was statistically significant higher in tenpin bowlers than inactive non-bowlers. Tenpin bowler group showed statistically significant higher mean value of isokinetic knee flexion PT (p ˂ 0.05) at the angular velocity of 60⁰.s- 1 at the non-dominant leg compared to inactive non-bowlers control group. Tenpin bowler group also showed statistically borderline significant higher mean values of isokinetic knee flexion PT (p = 0.057) and PT/BW (p = 0.059) at 300⁰.s-1 at the non-dominant leg compared to inactive non-bowlers control group. Nevertheless, non-statistically significant higher values of isokinetic shoulder extension PT, PT/BW AVG.P at 60⁰.s-1 and 300⁰.s-1 at dominant arms were observed in tenpin bowlers compared to inactive nonbowler controls. Similarly, non-statistically significant higher values of isokinetic knee extension and flexion PT, PT/BW and AVG.P at 300⁰.s-1 of dominant and non-dominant legs were observed in tenpin bowlers compared to inactive non-bowler controls. In addition, non-statistically significant higher hand grip strength of dominant arm, back and leg strength and flexibility were observed in tenpin bowlers than inactive non-bowler controls. There were no statistically significant differences in all the bone SOS measured parameters in dominant and non-dominant arms and legs of tenpin bowler and inactive non-bowler controls. This study results implying that participation in tenpin bowling can improve physical fitness component compared to sedentary lifestyle in Malaysian males.